Thermal conversion of black liquor solids to monomeric aromatic hydrocarbons based on synergistic catalysis by Na compounds and HZSM-5. Issue 20 (21st September 2022) - Chang, Guozhang; Wang, Juzheng; Cui, Weiwei; Wang, Cuiping; Zhang, Jian
Abstract : This work assessed the feasibility of producing aromatic hydrocarbons from catalytic pyrolysis of a black liquor solid (BLS) and the lignin extracted from the BLS (BLL). Abstract : This work assessed the feasibility of producing aromatic hydrocarbons from catalytic pyrolysis of a black liquor solid (BLS) and the lignin extracted from the BLS (BLL). The results show that the addition of HZSM-5 could enhance the solid conversion for both BLS and BLL during the temperature-programmed pyrolysis process to produce more volatiles. Na compounds (Na2 CO3 or NaOH) could promote the formation of H2 and phenols in BLL pyrolysis, leading to generation of more monomeric aromatic hydrocarbons (MAHs) from the strengthened hydrodeoxygenation effect of HZSM-5. Synergistic effects on the release of volatiles were observed during BLL pyrolysis when applying Na2 CO3 combined with HZSM-5. The yields of MAHs obtained from the synergistic catalytic pyrolysis of BLL and BLS increased from 0.95% to 25.83%, and from 1.09% to 25.5%, respectively. This study implies that combined application of active metal components and zeolites would be a promising pathway for facilitating MAH production from the pyrolysis of BLL or other biomass materials.